Three new species of the feather mite subfamily Ingrassiinae (Acariformes: Xolalgidae) from shearwaters and petrels (Procellariiformes: Procellariidae) - Stefan, Laura M.; Gómez-Díaz, Elena; Mironov, Sergey (Zootaxa, 2013)
Three new species of the feather mite subfamily Ingrassiinae (Acariformes: Astigmata: Xolalgidae) are described from shearwaters and petrels (Procellariiformes: Procellariidae) in the North-East of Atlantic Ocean: Ingrassia calonectris sp. n. from Calonectris borealis (Cory) (type host) and Calonectris edwardsii (Oustalet), Ingrassia micronota sp. n. and Ope-tiopoda bulweriae sp. n. from Bulweria bulwerii (Jardine and Selby).